Strategic evaluation of Quezon City Library and Information Center CaféLIB - Razal, Johannah Mae O. (School of Library and Information Studies, University of the Philippines Diliman, 2015)
This study was conducted to evaluate Café@Lib of the Quezon City Public Library using three complementary methods. These methods are SWOT analysis, environmental scanning and three of Michael Porters' 5 forces analysis - threat of new entrant, threat of substitute product and services, and rivalry among existing competitors.